Solid waste foundation surrounding rock reinforcement grouting material and preparation method thereof

By using grouting materials prepared from industrial solid waste resources such as low carbon activated powder and metakaolin, the problem of low strength of existing grouting materials is solved, the effect of efficient reinforcement of surrounding rocks is achieved, and good mechanical properties and environmental protection advantages are provided.

CN118993689BActive Publication Date: 2025-02-28TECH INFORMATION RES INST OF BUILDING MATERIALS IND
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411202496.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-02-28
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

The overall strength of existing surrounding rock reinforcement grouting materials is not high, and it is difficult to meet the engineering needs under complex geological conditions.

Method used

Low-carbon active powders and metakaolin are used as the main cementitious materials, combined with modified water-absorbing resin and appropriate amounts of admixtures, and ultra-fine particle size grouting materials are prepared by grinding to achieve complete replacement of cement.

Benefits of technology

The prepared grouting materials have excellent mechanical properties, high stone rate and low cost, and can effectively reinforce weak crushed surrounding rocks and improve the shear resistance and deformation stability of surrounding rocks.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of construction building materials, and in particular to a solid waste foundation surrounding rock reinforcement grouting material and a preparation method thereof. Industrial solid waste is modified and ground to prepare low-carbon active powder, which is combined with kaolin as a cementitious material. By adjusting the variety of admixtures, a grouting reinforcement material with good mechanical properties, high solidity rate and low cost is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of construction building materials, and in particular to a solid waste foundation rock reinforcement grouting material and a preparation method thereof. Background Art

[0002] The surrounding rock of underground projects is complex and varied, and different geological conditions require different types and performance requirements for grouting materials. When reinforcing weak and broken surrounding rock, it is necessary to select grouting materials suitable for the project itself and study the properties of the grouting materials to achieve good reinforcement results. Grouting technology can enhance the bonding strength of weak and broken surrounding rock, improve the porosity of the surrounding rock, and enhance the shear resistance of the surrounding rock structure. Ultimately, it improves the mechanical properties of the surrounding rock mass, enhances the deformation stability of the surrounding rock, and reduces the possibility of engineering disasters.

[0003] Currently, most grouting materials used for surrounding rock reinforcement are based on ordinary Portland cement. Exploring alternative industrial solid waste resources to replace cement, reducing costs and enabling resource reuse, is becoming a mainstream trend. By rationally utilizing industrial waste residues, not only can resources be conserved and waste be transformed into valuable resources, but it can also contribute to environmental protection.

[0004] Patent CN 114573301 A uses Portland cement, silica fume, and high-density ore as binders, supplemented by a water reducer, to prepare a new composite cement-based grouting material with a maximum strength of 27 MPa after 28 days. Patent CN 116655317 A uses ordinary Portland cement, ultrafine slag powder, and silica fume as the main binders, supplemented by a water reducer, to prepare a high-strength, low-viscosity grouting material with a maximum compressive strength of 27 MPa after 28 days. Patent CN 116715477 A uses ultrafine Portland cement as the binder, supplemented by a water reducer, an expansive agent, an accelerator, and acrylic fiber, to prepare a polypropylene fiber-reinforced ultrafine cement-based grouting full-length anchoring material, exhibiting higher anchoring strength, enhanced deformation coordination, and better durability.

[0005] Patent CN 113185176 A uses microsilica powder and / or fly ash as cementitious materials. No cement is added in this patent. Instead, rubber powder is used as an additive to prepare a modified cement-based grouting material. The grouting material does not disperse in water, but its maximum 28d strength is only 25 MPa, and its overall strength is not high. Summary of the Invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a solid waste foundation rock reinforcement grouting material, which utilizes industrial solid waste for modified grinding to prepare low-carbon active powder, and combines it with kaolin as a cementitious material. By adjusting the type of admixture, a grouting reinforcement material with good mechanical properties, high solidity rate and low cost is prepared.

[0007] Specifically, the solid waste foundation surrounding rock reinforcement grouting material of the present invention is composed of the following raw materials in parts by weight:

[0008] 60-70 parts of low-carbon active powder, 15-25 parts of quartz powder, 8-15 parts of metakaolin, 0.1-2 parts of water reducer, 0.1-1 parts of modified water-absorbing resin, and 0.01-0.1 parts of phosphate.

[0009] Preferably, the low-carbon active powder preparation process is as follows: activated coal gangue, mineral powder, fly ash, polyol fatty acid ester, acrylamide-acrylic acid copolymer, and ethyl oxalate are mixed uniformly in a mass ratio of (5-6):(4-5):(1-2):(0.01-0.1):(0.01-0.1):(0.01-0.1) and then ground to obtain the powder. The present invention uses activated coal gangue, mineral powder, and fly ash as raw materials, adds a modifier, and then grinds them to obtain ultrafine-grained low-carbon active powder with good activity. By using the powder as the main cementitious material and combining it with metakaolin, it can completely replace cement to prepare surrounding rock reinforcement grouting materials.

[0010] Preferably, the modified water-absorbing resin is prepared by mixing cellulose ether, sodium acrylate-acrylamide copolymer, water, and an initiator in a mass ratio of (0.1-0.2):1:(70-80):(0.01-0.02), ultrasonically treating the mixture, adding a nano-SiO2 sol, stirring uniformly, and spray drying. The amount of nano-SiO2 sol added is 30-50% of the mass of the sodium acrylate-acrylamide copolymer. The modified water-absorbing resin can improve the workability of the grouting material slurry, increase the stone formation rate, and is more compatible with low-carbon active powders.

[0011] Preferably, the activated coal gangue is obtained by calcining coal gangue at 680-720°C and rapidly cooling it.

[0012] Preferably, the polyol fatty acid ester is at least one of monoglycerol fatty acid ester and sorbitan fatty acid ester.

[0013] Preferably, the specific surface area of ​​the low carbon active powder is 900-1000 cm 2 / g.

[0014] Preferably, the quartz powder has a fineness of 100-120 mesh.

[0015] Preferably, the cellulose ether is at least one of hydroxypropyl methyl cellulose ether and hydroxyethyl cellulose ether.

[0016] Preferably, the initiator is ammonium persulfate.

[0017] Preferably, the water reducer is a polycarboxylic acid water reducer with a water reduction rate of ≥30%.

[0018] Preferably, the phosphate is at least one of dihydrogen phosphate and disodium hydrogen phosphate. The addition of phosphate can improve the dispersion effect of the low-carbon active powder.

[0019] The present invention also relates to a method for preparing the above-mentioned solid waste foundation rock reinforcement grouting material, which specifically comprises the following steps:

[0020] 1) Weigh each raw material by mass,

[0021] 2) Mix all the raw materials evenly and pack them.

[0022] The present invention also relates to the application of the above-mentioned solid waste foundation surrounding rock reinforcement grouting material. Specifically, water and grouting material powder are evenly mixed according to a water-to-material ratio of 0.3-0.4, and grouting construction can be carried out.

[0023] The present invention has the following technical advantages:

[0024] 1. The present invention uses low-carbon active powder with high activity, and the prepared grouting material has excellent mechanical properties.

[0025] 2. The modified water-absorbing resin of the present invention is beneficial to improving the workability of grouting materials, increasing the stone formation rate, and enhancing the grouting effect.

[0026] 3. The present invention uses industrial solid waste as the main raw material, which is energy-saving, environmentally friendly, and reduces costs and utilizes waste. DETAILED DESCRIPTION

[0027] In order to characterize the technical effect of the present invention, grouting materials were prepared with a water-to-material ratio of 0.3, and their compressive strength and stone rate were tested. The activated coal gangue was obtained by calcining and rapidly cooling the coal gangue at 700°C, and the low-carbon active powder was ground to a specific surface area of ​​more than 900 cm 2 / g, the water reducing agent used is polycarboxylic acid water reducing agent with a water reduction rate of 32%.

[0028] Example 1

[0029] The grouting material is characterized by being composed of the following raw materials in parts by weight:

[0030] 68 parts of low carbon active powder, 22 parts of quartz powder, 10 parts of metakaolin, 1.6 parts of water reducer, 0.5 parts of modified water-absorbing resin, 0.03 parts of disodium hydrogen phosphate,

[0031] The low-carbon active powder preparation process is as follows: activated coal gangue, mineral powder, fly ash, monoglyceride fatty acid ester, acrylamide-acrylic acid copolymer, and ethyl oxalate are uniformly mixed in a mass ratio of 5:5:1:0.07:0.05:0.09, and then ground to obtain the low-carbon active powder.

[0032] The modified water-absorbing resin preparation process comprises the following steps: mixing hydroxypropyl methylcellulose ether, sodium acrylate-acrylamide copolymer, water, and ammonium persulfate in a mass ratio of 0.2:1:78:0.01, ultrasonically treating the mixture, adding nano-SiO2 sol, stirring the mixture evenly, and spray drying the mixture to obtain the modified water-absorbing resin. The amount of nano-SiO2 sol added is 40% of the mass of the sodium acrylate-acrylamide copolymer.

[0033] After testing, the grouting material has good workability, no segregation or exudation, 1-day compressive strength of 5.9MPa, 7-day compressive strength of 19.5MPa, 28-day compressive strength of 42.2MPa, and stone rate of 97.6%.

[0034] Example 2

[0035] The grouting material is characterized by being composed of the following raw materials in parts by weight:

[0036] 70 parts of low carbon active powder, 20 parts of quartz powder, 12 parts of metakaolin, 1.8 parts of water reducer, 0.5 parts of modified water-absorbing resin, 0.04 parts of sodium dihydrogen phosphate,

[0037] The low-carbon active powder preparation process is as follows: activated coal gangue, mineral powder, fly ash, fatty acid sorbitan ester, acrylamide-acrylic acid copolymer, and ethyl oxalate are uniformly mixed in a mass ratio of 5:4.5:1.5:0.1:0.06:0.03, and then ground to obtain the low-carbon active powder.

[0038] The modified water-absorbing resin preparation process comprises the following steps: mixing hydroxyethyl cellulose ether, sodium acrylate-acrylamide copolymer, water, and ammonium persulfate in a mass ratio of 0.15:1:77:0.01, ultrasonically treating the mixture, adding nano-SiO2 sol, stirring the mixture evenly, and spray drying the mixture to obtain the modified water-absorbing resin. The amount of nano-SiO2 sol added is 40% of the mass of the sodium acrylate-acrylamide copolymer.

[0039] After testing, the grouting material has good workability, no segregation or exudation, 1-day compressive strength is 6.4MPa, 7-day compressive strength is 20.7MPa, 28-day compressive strength is 46.0MPa, and the stone rate is 99.3%.

[0040] Comparative Example 1

[0041] The grouting material is characterized by being composed of the following raw materials in parts by weight:

[0042] 68 parts of low carbon active powder, 22 parts of quartz powder, 10 parts of metakaolin, 1.6 parts of water reducer, 0.5 parts of modified water-absorbing resin, 0.03 parts of disodium hydrogen phosphate,

[0043] The low-carbon active powder preparation process is as follows: mineral powder, fly ash, monoglyceride fatty acid ester, acrylamide-acrylic acid copolymer, and ethyl oxalate are uniformly mixed in a mass ratio of 7:3:0.07:0.05:0.09, and then ground to obtain the low-carbon active powder.

[0044] The modified water-absorbing resin preparation process comprises the following steps: mixing hydroxypropyl methylcellulose ether, sodium acrylate-acrylamide copolymer, water, and ammonium persulfate in a mass ratio of 0.2:1:78:0.01, ultrasonically treating the mixture, adding nano-SiO2 sol, stirring the mixture evenly, and spray drying the mixture to obtain the modified water-absorbing resin. The amount of nano-SiO2 sol added is 40% of the mass of the sodium acrylate-acrylamide copolymer.

[0045] After testing, the grouting material has good workability, no segregation or exudation, 1-day compressive strength is 4.5MPa, 7-day compressive strength is 15.1MPa, 28-day compressive strength is 37.2MPa, and the stone rate is 96.2%.

[0046] Comparative Example 2

[0047] The grouting material is characterized by being composed of the following raw materials in parts by weight:

[0048] 68 parts of low carbon active powder, 22 parts of quartz powder, 10 parts of metakaolin, 1.6 parts of water reducer, 0.5 parts of modified water-absorbing resin, 0.03 parts of disodium hydrogen phosphate,

[0049] The low-carbon active powder preparation process is as follows: activated coal gangue, mineral powder, fly ash, and monoglycerol fatty acid ester are mixed uniformly in a mass ratio of 5:5:1:0.15 and then ground to obtain the low-carbon active powder.

[0050] The modified water-absorbing resin preparation process comprises the following steps: mixing hydroxypropyl methylcellulose ether, sodium acrylate-acrylamide copolymer, water, and ammonium persulfate in a mass ratio of 0.2:1:78:0.01, ultrasonically treating the mixture, adding nano-SiO2 sol, stirring the mixture evenly, and spray drying the mixture to obtain the modified water-absorbing resin. The amount of nano-SiO2 sol added is 40% of the mass of the sodium acrylate-acrylamide copolymer.

[0051] After testing, the grouting material has good workability, no segregation or exudation, 1-day compressive strength is 3.2MPa, 7-day compressive strength is 11.4MPa, 28-day compressive strength is 34.0MPa, and the stone rate is 95.5%.

[0052] Comparative Example 3

[0053] The grouting material is characterized by being composed of the following raw materials in parts by weight:

[0054] 68 parts of low carbon active powder, 22 parts of quartz powder, 10 parts of metakaolin, 1.6 parts of water reducer, 0.5 parts of sodium acrylate-acrylamide type water-absorbing resin, 0.03 parts of disodium hydrogen phosphate,

[0055] The low-carbon active powder preparation process comprises the following steps: uniformly mixing activated coal gangue, mineral powder, fly ash, monoglyceride fatty acid ester, acrylamide-acrylic acid copolymer, and ethyl oxalate in a mass ratio of 5:5:1:0.07:0.05:0.09, and then grinding the mixture to obtain the low-carbon active powder.

[0056] After testing, the grouting material has general workability, exudation, 1-day compressive strength of 3.9MPa, 7-day compressive strength of 13.6MPa, 28-day compressive strength of 35.2MPa, and stone rate of 91.1%.

[0057] Comparative Example 4

[0058] The grouting material is characterized by being composed of the following raw materials in parts by weight:

[0059] 68 parts of low carbon active powder, 22 parts of quartz powder, 10 parts of metakaolin, 1.6 parts of water reducer, 0.5 parts of modified water-absorbing resin, 0.03 parts of disodium hydrogen phosphate,

[0060] The low-carbon active powder preparation process is as follows: activated coal gangue, mineral powder, fly ash, monoglyceride fatty acid ester, acrylamide-acrylic acid copolymer, and ethyl oxalate are uniformly mixed in a mass ratio of 5:5:1:0.07:0.05:0.09, and then ground to obtain the low-carbon active powder.

[0061] The modified water-absorbing resin is prepared by mixing hydroxypropyl methylcellulose ether, sodium acrylate-acrylamide copolymer, water, and ammonium persulfate in a mass ratio of 0.2:1:78:0.01, ultrasonically treating the mixture, and spray drying the mixture to obtain the modified water-absorbing resin.

[0062] After testing, the grouting material has general workability, slight water exudation, 1-day compressive strength of 4.4MPa, 7-day compressive strength of 14.9MPa, 28-day compressive strength of 37.7MPa, and stone rate of 92.6%.

[0063] Comparative Example 5

[0064] The grouting material is characterized by being composed of the following raw materials in parts by weight:

[0065] 68 parts of low carbon active powder, 22 parts of quartz powder, 10 parts of metakaolin, 1.6 parts of water reducer, 0.5 parts of modified water-absorbing resin,

[0066] The low-carbon active powder preparation process is as follows: activated coal gangue, mineral powder, fly ash, monoglyceride fatty acid ester, acrylamide-acrylic acid copolymer, and ethyl oxalate are uniformly mixed in a mass ratio of 5:5:1:0.07:0.05:0.09, and then ground to obtain the low-carbon active powder.

[0067] The modified water-absorbing resin preparation process comprises the following steps: mixing hydroxypropyl methylcellulose ether, sodium acrylate-acrylamide copolymer, water, and ammonium persulfate in a mass ratio of 0.2:1:78:0.01, ultrasonically treating the mixture, adding nano-SiO2 sol, stirring the mixture evenly, and spray drying the mixture to obtain the modified water-absorbing resin. The amount of nano-SiO2 sol added is 40% of the mass of the sodium acrylate-acrylamide copolymer.

[0068] After testing, the grouting material has general workability, slight compaction, 1d compressive strength of 5.1MPa, 7d compressive strength of 16.3MPa, 28d compressive strength of 38.0MPa, and stone rate of 95.6%.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A solid waste foundation rock reinforcement grouting material, characterized in that , composed of the following raw materials in parts by weight: 60-70 parts of low carbon active powder, 15-25 parts of quartz powder, 8-15 parts of metakaolin, 0.1-2 parts of water reducer, 0.1-1 parts of modified water-absorbing resin, 0.01-0.1 parts of phosphate, The low-carbon active powder preparation process comprises: uniformly mixing activated coal gangue, mineral powder, fly ash, polyol fatty acid ester, acrylamide-acrylic acid copolymer, and ethyl oxalate in a mass ratio of (5-6):(4-5):(1-2):(0.01-0.1):(0.01-0.1):(0.01-0.1), and then grinding to obtain the low-carbon active powder. The preparation process of the modified water-absorbing resin is as follows: cellulose ether, sodium acrylate-acrylamide copolymer, water and initiator are mixed in a mass ratio of (0.1-0.2):1:(70-80):(0.01-0.02), ultrasonic treatment is performed, nano-SiO2 sol is added, stirred evenly, and spray-dried to obtain the modified water-absorbing resin, wherein the amount of nano-SiO2 sol added is 30-50% of the mass of the sodium acrylate-acrylamide copolymer.

2. The solid waste foundation rock reinforcement grouting material according to claim 1, characterized in that The activated coal gangue is obtained by calcining the coal gangue at 680-720°C and rapidly cooling it.

3. The solid waste foundation surrounding rock reinforcement grouting material according to claim 1, characterized in that , the polyol fatty acid ester is at least one of monoglycerol fatty acid ester and sorbitan fatty acid ester.

4. The solid waste foundation rock reinforcement grouting material according to claim 1, characterized in that The specific surface area of ​​the low carbon active powder is 900-1000cm 2 / g.

5. The solid waste foundation rock reinforcement grouting material according to claim 1, characterized in that , the quartz powder fineness is 100-120 mesh.

6. The solid waste foundation rock reinforcement grouting material according to claim 1, characterized in that , the cellulose ether is at least one of hydroxypropyl methyl cellulose ether and hydroxyethyl cellulose ether.

7. The solid waste foundation rock reinforcement grouting material according to claim 1, characterized in that , the initiator is ammonium persulfate.

8. The solid waste foundation rock reinforcement grouting material according to claim 1, characterized in that , the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is ≥30%.

9. The solid waste foundation rock reinforcement grouting material according to claim 1, characterized in that , the phosphate is at least one of dihydrogen phosphate and disodium hydrogen phosphate.

10. The method for preparing the solid waste foundation surrounding rock reinforcement grouting material according to any one of claims 1 to 9, characterized in that , including the following steps: 1) Weigh each raw material by mass, 2) Mix all the raw materials evenly and package.

Citation Information

Patent Citations

  • Cement-based grouting material modifier, cement-based grouting material and preparation method

    CN113185176A

  • Preparation method of high-strength low-viscosity grouting material

    CN116655317A

  • Polypropylene fiber reinforced superfine cement-based grouting full-length anchoring material and preparation method thereof

    CN116715477A

  • Method for preparing high-activity gelling material by activation of coal gangue

    CN108002721A

  • Solid waste source high-activity powder base slurry and preparation method thereof

    CN116947429A